The Effect of KNO3 Fertilizer Dosage and Paclobutrazol Concentration on The Growth and Yield of Long Bean (Vigna sinensis L.) - Sintha Dayu Aringgani; Djarwatiningsih Djarwatiningsih; Agus Sulistyono (The University of Lampung, 2025)
Long bean production has decreased in Indonesia due to uncertain seasonal factors, such as long dry seasons and short rainy seasons. Long bean production has decreased due to inappropriate and optimal cultivation techniques. Several efforts can be made to overcome the problem of decreasing long bean productivity by fertilizing and applying growth regulators. The aim of this research is to understand the combined effect of KNO₃ fertilizer doses and paclobutrazol concentrations on the growth and yield of long bean plants. Thise research was conducted in Ketawang Village, Nganjuk, East Java. The research was a factorial experiment with Split Plot Design consisted of two treatment levels, namely KNO₃ fertilizer dose (0 g/plant, 8 g/plant, 10 g/plant and 12 g/plant) and paclobutrazol concentration (0 ppm, 150 ppm, 175 ppm and 200 ppm). The combination of 10 g/plant KNO₃ + 150 ppm paclobutrazol influences the growth and yield of long bean plants, however the application of KNO₃ fertilizer alone has no effect on the growth and yield of long bean plants. Keywords: Giberelin, Growth regulator, Harvest, Nutrient, Retardant.